Electrochemical Detection of Circulating Tumor Cells Based on DNA Generated Electrochemical Current and Rolling Circle Amplification - Shen, Congcong; Liu, Shuping; Li, Xiaoqing; Yang, Minghui (Analytical chemistry (Washington), 2019)
Circulating tumor cells (CTCs) are important indicators for tumor diagnosis and tumor metastasis. However, the extremely low levels of CTCs in peripheral blood challenges the precise detection of CTCs. Herein, we report DNA generated electrochemical current combined with rolling circle amplification (RCA) as well as magnetic nanospheres for highly efficient magnetic capture and ultrasensitive detection of CTCs. The antiepithelial cell adhesion molecule (EpCAM) antibody-modified magnetic nanospheres were used to capture and enrich CTCs. The following binding of an aptamer onto the CTC surface and the subsequent RCA assembled a significant amount of DNA molecules onto the electrode. The reaction of the DNA molecules with molybdate can then form redox molybdophosphate and produce an electrochemical current. Using the breast cancer cell MCF-7 as a model, the sensor displays good performances toward detection of MCF-7 that was spiked into peripheral blood. The signal amplification strategy integrated with a magnetic nanosphere platform exhibits good performance in the efficient capture and detection of CTCs, which may find wide potential in cancer diagnostics and therapeutics.